Novel Photoresponsive Linear, Graft, and Comb‐Like Copolymers with Azobenzene Chromophores in the Main‐Chain and/or Side‐Chain: Facile One‐Pot Synthesis and Photoresponse Properties. Issue 17 (22nd June 2015) - Ding, Liang; Qiu, Jun; Li, Juan; Wang, Chengshuang; Wang, Lingfang
<x xml:space="preserve">Abstract</x> Novel photoresponsive linear, graft, and comb‐like copolymers with azobenzene chromophores in the main‐chain and/or side‐chain are prepared via a sequential ring‐opening metathesis polymerization (ROMP) and head‐to‐tail acyclic diene metathesis (ADMET) polymerization in a one‐pot procedure using Grubbs ruthenium‐based catalysts. The diluted solutions of these as‐prepared copolymers containing azobenzene chromophores exhibit photochemical trans–cis isomerization under the irradiation of UV light, followed by their cis–trans back‐isomerization in visible light. The rates of photoisomerization are found to be slower than those of back‐isomerization, and the rate for the comb‐like copolymer is found to be from 3 to 7 times slower than that obtained for the linear or graft copolymer. This is ascribed to the differences in structure of the copolymers and the specific location of azobenzene chromophores in the copolymer, which favor a side‐chain graft structure.